'Common language' and proficiency tests: a critical examination of registration requirements for Australian registered migration agents. Issue 1 (2nd January 2021) - Smith-Khan, Laura
ABSTRACT: Registered Migration Agents (RMAs), the practitioners who assist with Australian visa applications and appeals, play a crucial role in navigating these complex legal procedures. RMAs' registration requirements, including those relating to English language proficiency (ELP), have thus garnered much attention, leading to government-commissioned reviews and inquiries, and amendments to regulations. The most recent changes have attracted scrutiny by the Australian Parliamentary Joint Committee on Human Rights, due to the unequal burden to prove ELP placed on different applicants based on their backgrounds. However, these new requirements ultimately came into force without the government satisfying the Committee that they were human rights-compliant. This article examines the most recent ELP rules for RMAs and the Immigration Minister's justifications for these. Drawing on sociolinguistic scholarship, it finds that rules requiring general ELP tests, and categorically exempting certain applicants from testing, rely on problematic assumptions about the nature of language, and are therefore unnecessarily discriminatory. Given the government aims to ensure specific communicative competencies within the migration advice setting, the analysis concludes that these specific competencies should be the focus of any required assessment.